Collective psychological ownership and the rise of reactionary counter‐movements defending the status quo. (18th September 2020) - Selvanathan, Hema Preya; Lickel, Brian; Jetten, Jolanda
Abstract : Social movements pushing for social change are often met with reactionary counter‐movements that defend the status quo. The present research examined this interplay by focusing on the role of racial majority group members claiming collective psychological ownership. We examined collective ownership that stems from being native to the land and from being founders of the nation. Study 1 found that in Malaysia, the Malay majority group endorsed more native ownership than Chinese and Indian minorities, which in turn predicted greater threat in response to protests demanding electoral reforms and subsequently greater support for a reactionary pro‐government movement. Situated in the United States, Study 2 found that the more that White Americans endorsed founder ownership beliefs, the more they reported negative attitudes towards the Black Lives Matter protests, which in turn predicted more support for White nationalistic counter‐protests. This effect was stronger among White people compared to people of colour. Study 3 examined both founder and native ownership in Australia. Founder (but not native) ownership beliefs predicted more negative attitudes towards Invasion Day protests, which subsequently predicted more support for counter‐protests defending Australia Day celebrations. Implications of culture‐specific beliefs about collective ownership for social movement research are discussed.